Metadata and semantic research : 13th International Conference, MTSR 2019, Rome, Italy, October 28-31, 2019, Revised selected papers /: 13th International Conference, MTSR 2019, Rome, Italy, October 28-31, 2019, Revised selected papers. (2019) - Unknown
No abstract available